Palm oil cake for cattle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The Malaysian veterinary authorities have tried feeding 2000 cattle, mainly Friesian and Sahiwal crossbreeds, with palm oil cake. The results are good provided the oil content of the cake remains below 2 to 3 %. On the basis of these trials it is...